Rebuilding of Beyoglu-Istiklal Street: a comparative analysis of urban transformation through sections along the street 2004-2014 - Tekin, İlke; Akgün, Asiye Gültekin (Middle East Technical Univ, Middle East Technical Univ, Fac Architecture, Inonu Bulvarı, Ankara, 06531, Turkey, 2017)
The history of marketing urban spaces through showcasing them like commodities has started after the Second World War. The strategists, behind these window displays, are actors possessing political and economic capital. Urban transformation projects occurred as a consequence of the capital orienting to urban land, which brought about upheavals in socio-spatial structure. Considering the urban transformation projects in Turkey, Istanbul, as a city in the running to become a global city, is the preeminent showcase with its historical, cultural and economic potentials for the political and economic actors. The macro-scale urban transformation projects seen in Istanbul after 2000s can be observed on the micro scale in the rebuilding of Istiklal Street as the main artery in Beyoglu quarter, which is one of the historic city centers. In this context, this article analyzes the urban transformation initiatives in Istanbul focusing on the urban transformation of Istiklal Street and its immediate vicinity which has gained momentum from 2005. This research is predicated on a comparative spatial analysis of Istiklal Street. Sixty cross-sections were obtained from Taksim Square to Tunel Square in 2004 with a view to analyze the spatial use patterns on Istiklal Street. The study has been replicated in 2014 in order to analyze spatial transformation. In this regard, the research discusses the spatial transformation appeared in a decade, between 2004 and 2014, through the influences of capital and politics; and it presents the urban planning strategies oriented to global city, neoliberal policies and cultural tourism in Istanbul and the reflections of them in Beyoglu quarter. The spatial transformation of Istiklal Street is evaluated through the analysis per square meter of the cross-sectioned buildings, spatial comparisons, media scanning for monitoring actors and discourses, and interviews with landlords and tenants. In relation to the phenomenon of globalization, the paper deals with the transformation of spaces covered by culture, finance, informatics and tourism sectors, and catering and shopping spaces appealing to service these sectors with reference to the phenomenon of cultural tourism.
Keywords: Global city; neoliberalism; cultural tourism; Istiklal Street; spatial transformation; Istanbul; Construction